Biobank as a key component of supporting research in phthisiology and infectious diseases - T. V. Umpeleva; D. V. Vakhrusheva; S. N. Skornyakov (Кардиоваскулярная терапия и профилактика, 2022)
Conducting fundamental and clinical research in the field of tuberculosis is an important step towards reducing related morbidity and mortality, but access to a sufficient number of high-quality samples required for research is an unsolved problem in Russia. This review is devoted to biobanking as a key component of modern research in personalized medicine, as well as to the status and prospects for developing this area in phthisiology and infectious diseases combined with tuberculosis.